(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we look at a dual description of life distributions based on entropy that is realistic to past lifetimes. The formula for (t) is used, The formula for past entropy of the Weibull distribution is found and used for the Application portion, which extends the improbability about its previous. Using mathematical models, we discovered various probability density functions and cumulative distribution functions for cortisol and androgen development. Finally, we conclude that the corresponding mathematical results have been obtained, and the medical solutions have been analysed.